The ethanol extract of Syzygium cumini exhibits cytotoxic potentials against breast cancer cells due to antioxidant properties: Cytotoxic and antioxidant activity of Syzygium cumini - Pundi, Krishna; Ramesh, C; Rawal, Pinkey; Sowmya, B.A. (Journal of Drug Delivery and Therapeutics, 2023)
The present investigation was designed to evaluate in vitro cytotoxic potentials of ethanol extract of Syzygium cumini against breast cancer cells and also estimate its antioxidant activity. The ethanol extract of Syzygium cumini was prepared by successive solvent extraction process using sox-let apparatus. The ethanol extract was evaluated for its in-vitro anticancer potentials against MCF-7  human breast cancer cell lines by MTT assay and concentration of the ethanol extract required to inhibit 50% of cell growth (IC50) was recorded. To determine antioxidant properties of the extract, superoxide scavenging, lipid peroxidation and DPPH methods were used and IC50 values of extracts were noted. In current study, ethanol extract of Syzygium cumini has shown anticancer property by exhibiting significant IC50 values against growth of breast cancer cell growth. The extract has also shown significant IC50 values in superoxide scavenging, lipid peroxidation and DPPH methods and antioxidant activity was comparable to standard drug ascorbic acid. The results obtained from the present research work suggested that the ethanol extract of Syzygium cumini possess significant in vitro cytotoxic potentials against breast cancer cells. The results also suggested that the ethanol extract have in vitro antioxidant properties.Keywords: Anticancer activity, Syzygium cumini, IC50 value, MTT assay and antioxidant activity.